THE DIPLOMATIC RELATIONS BETWEEN THE REPUBLIC OF MACEDONIA AND THE REPUBLIC OF GREECE AFTER SIGNING OF THE INTERIM AGREEMENT FROM 1995 TO 2008 - Adji-Andov, Miroslav (Journal of process management and new technologies, 2018)
Diplomacy is an art and/or practice of negotiating between certain states leaders. Namely, all international agreements are commonly negotiated between diplomats, before those same contracts are accepted by national politicians. International diplomacy in the world system also takes place through numerous events, personal conversations between diplomats, electronic communications, etc. In fact, an important element of diplomacy is working on current problems between states through negotiating. Most often, the leaders of certain states can not agree on some issues related to trade or foreign policy, or other issues of relevance to them, so here instead of using violence to resolve a specific dispute, diplomacy is used to find out solution. There are numerous cases of diplomacy in international relations, as well as case studies of invested diplomatic efforts between different countries. Although diplomacy has been an integral part of international relations for centuries, but still remains the most critical component in international relations. In this paper, we focus on perceiving the overall diplomatic relations between the Republic of Macedonia and the Republic of Greece after signing of the interim agreement from 1995 to 2008, on the other hand.